Estimating the Transmittance of Visible Solar Radiation in the Upper Ocean Using Secchi Disk Observations. Issue 3 (4th March 2019) - Lee, Zhongping; Shang, Shaoling; Du, Keping; Lin, Gong; Liu, Tongtong; Zoffoli, Laura
Abstract: Penetration of visible solar radiation (VSR) drives heating and phytoplankton photosynthesis in the upper water column; thus, it is always important to accurately describe the vertical distribution of VSR in the oceans. Before the invention and application of modern optical‐electronic instruments to measure the vertical profiles of VSR, the transmittance of VSR from surface to deeper ocean ( T VSR ) was commonly estimated based on water types and subsequently incorporated in dynamic ocean circulation models. However, the measurement of Secchi disk depth ( Z SD ) has been carried out since the 1860s and there are about a million of Z SD data available for the global oceans. Because Z SD represents a measure of water's transparency, here we present a scheme based on radiative transfer to accurately estimate T VSR with Z SD as the sole input. It is found that the median ratios between modeled and measured T VSR are ~0.8–1.0 for T VSR in a range of 1–100% for measurements made in coastal waters and oceanic gyres. However, this median ratio spans ~0.04–1.0 for the same measurements when the classical water‐type‐based model was applied. These results suggest a great advantage, and potentially significant impact, in incorporating the volumetric Z SD data to model the dynamic ocean–atmosphere systems in the past 100+ years. Plain Language Summary: Based on radiative transfer and using numerically simulated data, the transmittance ( T VSR ) of visible solar radiation (VSR) is modeled as a function of Secchi disk depth ( Z SD ). This scheme was further evaluated using data from numerical simulations and from field measurements where Z SD spans a range of ~1–75 m. For waters from coastal to super blue oceanic gyres, the modeled T VSR agree with measured T VSR very well for T VSR greater than 1%. For the same data set, however, the modeled T VSR can be 20 times lower than measured T VSR for oceanic waters when it was estimated based on the traditional water‐type approach. Better modeled T VSR can improve general ocean circulation models, which opens a door to better study the ocean–atmosphere systems in the past decades to a century with the large volume of Z SD data. Key Points: A model based on radiative transfer and Secchi depth ( Z SD ) is developed to estimate the transmittance of visible solar radiation The estimated transmittance with Z SD as input agrees very well with measured values, and significantly better than the water‐type scheme The scheme offers an opportunity to accurately estimate the transmittance of solar radiation in the upper ocean based on century‐long Z SD data